Pengenalan Pendidikan Antikorupsi Pada Siswa SDN 2 Gisting Permai Melalui Metode Bermain - Sulthon, M. Rijal; Dalman, Dalman; Febriyanti, In; Permata, Niken Ayu; Wulandari, Woro; Akbar, M. Zainur; Syahmalia, Nayanda; Ayu, Raden (Abdimas Indonesian Journal, 2024)
Problem Indication SDN 2 Gisting Permai students' understanding of anti-corruption education is still low, due to the curriculum that has not been integrated, conventional learning methods, and the lack of interesting learning resources. Objective To introduce anti-corruption education to students of SDN 2 Gisting Permai through the method of playing situation cards. Method Adopted Qualitative case study approach with problem-based learning and situation card game technique. 57 grade 6 students were involved. The results found that students' understanding and attitude towards anti-corruption increased significantly after the activity. The situation card game method proved effective in instilling anti-corruption values. The activity also had a positive impact on students' daily behavior at school. The application of similar methods can be carried out in other schools to create a young generation with integrity.